2018
DOI: 10.1144/sjg2017-010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage pyrite genesis and epigenetic selenium enrichment of Greenburn coals (East Ayrshire)

Abstract: Carboniferous coals of the Ayrshire Coalfield are enriched in selenium (Se) relative to average UK and world compositions, substituting for sulphur in pyrite. Greenburn surface mine coals are characterized by syngenetic concretionary pyrite (c. 15% total area), occurring as bedding-parallel banding, and later-formed (epigenetic) cross-cutting pyrite in cleats (c. 9% total area). In these, sulphur isotope compositions for both syngenetic and epigenetic pyrite include isotopically light and heavy variants, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Causes of thermal maturity in coal, such as igneous intrusions heating the strata, may also be accompanied by trace element‐carrying hydrothermal fluids percolating through coals, precipitating as pyrite. Dissolved metals in fluids can enhance Se and Te content of coals and have been suggested for Carboniferous coals in Ayrshire (Bullock et al, ) and Jurassic coals in Brora (Bullock et al, ). The close proximity of the South Wales, Cumberland, and Northumberland coalfields to granitic intrusions (e.g., Shap and Skiddaw granites of Cumberland, Dartmoor granite in southwest England, Weardale granite in northeast England), associated deformation which produced a series of faults through the coal strata (forming cleat systems), or later Variscan activity (in the case of South Wales), may have provided a source and/or flow pathway for hot metal‐rich fluids and subsequent increased maturity and trace element enrichment to these coals (see also Gayer et al, ; Turner & Richardson, ).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Causes of thermal maturity in coal, such as igneous intrusions heating the strata, may also be accompanied by trace element‐carrying hydrothermal fluids percolating through coals, precipitating as pyrite. Dissolved metals in fluids can enhance Se and Te content of coals and have been suggested for Carboniferous coals in Ayrshire (Bullock et al, ) and Jurassic coals in Brora (Bullock et al, ). The close proximity of the South Wales, Cumberland, and Northumberland coalfields to granitic intrusions (e.g., Shap and Skiddaw granites of Cumberland, Dartmoor granite in southwest England, Weardale granite in northeast England), associated deformation which produced a series of faults through the coal strata (forming cleat systems), or later Variscan activity (in the case of South Wales), may have provided a source and/or flow pathway for hot metal‐rich fluids and subsequent increased maturity and trace element enrichment to these coals (see also Gayer et al, ; Turner & Richardson, ).…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, Se has been shown to be more abundant in early forms of pyrite (Large et al, ). However, late stage epigenetic fluids are also known to be responsible for high concentrations of trace elements in some coals (Bullock et al, ; Diehl et al, ; Spears & Tewalt, ; Yudovich & Ketris, ). The presence of pyrite infilling cleats indicates a later period of formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations